Pt nanoparticle-loaded porous SiC catalyst and application thereof in cinnamyl aldehyde hydrogenation reaction
By loading Pt nanoparticles on the SiC catalyst and regulating the structure and performance of the catalyst through chemical etching and vacuum rotary distillation technology, the problem of low selectivity in the selective hydrogenation reaction of cinnamaldehyde is solved, and efficient preparation of cinnamon alcohol is achieved.
Patent Information
- Application Number
- CN202411826937.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-12
- Publication Date
- 2025-03-18
- Estimated Expiration
- 2044-12-12
AI Technical Summary
In the prior art, in the selective hydrogenation reaction of cinnamaldehyde, the selectivity of cinnamol is low, which is difficult to reach more than 90%, and it is difficult to control the hydrogen overflow intensity on the surface of SiC catalyst.
The porous SiC catalyst supported by Pt nanoparticles is used to form a porous structure through chemical etching of hydrofluoric acid and nitric acid, and the Pt ions are evenly dispersed by vacuum evaporation, and then in-situ reduction is performed to regulate the hydrogen overflow capacity of the catalyst.
The selectivity of cinnamaldehyde hydrogenation reaction is significantly improved, the yield of cinnamon alcohol is improved, the catalytic activity is better, and the high selectivity of cinnamon alcohol products is achieved.
Smart Images

Figure CN119633863A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of cinnamaldehyde hydrogenation reaction, and in particular to a Pt nanoparticle-loaded porous SiC catalyst and application thereof in cinnamaldehyde hydrogenation reaction. Background Art
[0002] Cinnamyl alcohol is an important chemical raw material and synthetic intermediate, which is widely used in many fields such as flavors and fragrances, organic synthesis, and health care. Selective hydrogenation of cinnamaldehyde is a green method for synthesizing cinnamyl alcohol, which has great application prospects. However, cinnamaldehyde contains two reducible functional groups, C=C bond and C=O bond, and the bond energy of C=C bond is lower than that of C=O bond. Therefore, it is a challenging problem to selectively control the hydrogenation of C=O bond while keeping C=C bond unchanged.
[0003] Hydrogen overflow is a common phenomenon in important chemical processes such as catalysis and hydrogen storage. It mainly refers to the migration of active hydrogen from the metal to the carrier after hydrogen dissociates on the metal surface, which has a significant effect on the catalytic performance. The catalytic activity and hydrogenation selectivity of the catalyst itself can be effectively changed by regulating the hydrogen overflow effect of the catalyst. For example, Gao Z et al. enhanced the hydrogen overflow on the surface of Pt / SBA-15 by modifying organic matter on the surface of the carrier, thereby effectively improving its catalytic performance in the hydrogenation of cinnamaldehyde (ACS Catal. 2023, 13, 4003-4011).
[0004] SiC is a typical non-oxide semiconductor material with good thermal and electrical conductivity, high temperature resistance and acid-base corrosion resistance, and is a catalyst carrier material with great application prospects. SiC-based metal catalysts are used in a variety of hydrogenation reactions, and their surfaces show obvious hydrogen overflow phenomenon. However, it is difficult to control the hydrogen overflow intensity on the surface of SiC-based metal catalysts. Summary of the invention
[0005] The problem in the prior art is that the selectivity of cinnamyl alcohol in the conventional selective hydrogenation reaction of cinnamaldehyde is low and it is difficult to reach more than 90%. In view of the above technical problems, the present invention provides a porous SiC catalyst supported by Pt nanoparticles, and the preparation method thereof comprises the following steps:
[0006] (1) chemically etching polycrystalline silicon carbide with a mixed acid formed by hydrofluoric acid and concentrated nitric acid, washing with water, drying, and then calcining in air at 700-1100° C. for at least 3 hours. After calcination, soaking the calcined product in hydrofluoric acid to remove silicon dioxide, and finally washing with water to neutrality and drying to obtain a porous silicon carbide carrier;
[0007] (2) adding a porous silicon carbide carrier and chloroplatinic acid to deionized water, stirring evenly, placing in a rotary evaporator, vacuum evaporating at room temperature for at least 30 minutes, adding lysine solution dropwise into the rotary evaporator after the addition is complete, stirring for at least 30 minutes, then adding a reducing agent aqueous solution and hydrochloric acid dropwise into the rotary evaporator in sequence, stirring for at least 24 hours after the addition is complete, after the reaction is complete, filtering the reaction solution, washing with deionized water at least 3 times, washing with ethanol aqueous solution at least 3 times, and drying to obtain a porous SiC catalyst;
[0008] The usage ratio of the porous silicon carbide carrier to chloroplatinic acid, deionized water, lysine solution, reducing agent aqueous solution, and hydrochloric acid is 290-295 mg: 15-17 mg: 30 mL: 20 mL: 10 mL: 10 mL;
[0009] The lysine solution is a solution with a concentration of 0.5-0.55 mol / L formed by dissolving lysine in deionized water;
[0010] The reducing agent aqueous solution is a solution having a concentration of 0.3-0.4 mol / L obtained by adding the reducing agent into deionized water;
[0011] The concentration of the hydrochloric acid is 0.25-0.35 mol / L.
[0012] Preferably, the reducing agent is sodium borohydride.
[0013] Preferably, the volume ratio of hydrofluoric acid to nitric acid in the mixed acid is 3:1, the mass concentration of hydrofluoric acid is 40%, and the mass concentration of nitric acid is 65-68%.
[0014] Preferably, the etching temperature in step (1) is in the range of 60-120°C.
[0015] Preferably, the etching time in step (1) is 1-4 hours.
[0016] Preferably, the etching time in step (1) is 3 hours.
[0017] An application of a porous SiC catalyst supported by Pt nanoparticles comprises the following steps:
[0018] The porous SiC catalyst is placed in a stainless steel high-pressure reactor, an alcohol solvent and cinnamaldehyde are added, the high-pressure reactor is sealed and purged with hydrogen for 3 times, and then hydrogen is filled into the reactor to a pressure of 0.4-0.8 MPa. Then, the temperature of the reactor is heated to 30-60° C. while magnetic stirring, and the reaction is carried out by constant temperature stirring for 30-90 minutes. After the reaction is completed, cinnamyl alcohol is obtained after purification.
[0019] Preferably, the alcohol solvent includes at least one of ethanol, isopropanol, methanol and a mixed solvent of ethanol and water.
[0020] Preferably, the alcohol solvent is a mixed solvent formed by ethanol and water.
[0021] Preferably, the volume ratio of ethanol to water in the alcohol solvent is 9-9.5:0.5-1. More preferably, the volume ratio of ethanol to water in the alcohol solvent is 9:1.
[0022] The present invention has the following beneficial effects:
[0023] (1) The present invention etches polycrystalline silicon carbide to obtain a porous structure by an acid etching method, and adopts a vacuum rotary evaporation method to first uniformly disperse Pt ions into the pore structure of polycrystalline silicon carbide, and then uses a reducing agent to in-situ reduce the Pt ions in the pore structure of polycrystalline silicon carbide to obtain Pt nanoparticles. This method allows the Pt nanoparticles to be distributed more and more evenly in the pore structure of polycrystalline silicon carbide, and the catalytic activity of the obtained catalyst is more excellent, which is conducive to further improving the selectivity of the cinnamaldehyde hydrogenation reaction and significantly improving the yield of cinnamyl alcohol;
[0024] (2) The present invention has found that the catalytic activity of the porous SiC catalyst obtained by the present invention is not only related to the uniform dispersion of Pt ions in the pore structure of polycrystalline silicon carbide by the vacuum rotary evaporation method, but also affected by the acid etching time of polycrystalline silicon carbide. The experimental results show that for the method of the present invention, when the acid etching time is 3h, the catalytic activity of the porous SiC catalyst obtained is better than that of the porous SiC catalyst obtained by other etching times;
[0025] (3) The present invention utilizes an acid etching method to perform porous modification on polycrystalline SiC, and enhances the hydrogen overflow concentration on the surface of the obtained catalyst Pt / SiC by regulating the Si / C ratio on its surface. The Pt nanoparticles in the pores can preferentially adsorb and activate C=O bonds due to the steric effect, thereby achieving high activity of the obtained catalyst in the cinnamaldehyde hydrogenation reaction and high selectivity for the cinnamyl alcohol product. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] Figure 1 : HRTEM images of the catalyst supports in Example 1 and Comparative Examples 1-2 of the present invention.
[0027] Figure 2 : HRTEM image of Pt / SiC-3 obtained in Example 1 of the present invention.
[0028] Figure 3 : XRD patterns of the catalysts obtained in Example 1 and Comparative Examples 1-3 of the present invention. DETAILED DESCRIPTION
[0029] The present invention is described in detail below with reference to the examples. However, it should be understood that the following examples are only illustrative of the embodiments of the present invention, and are not intended to limit the scope of the present invention.
[0030] Example 1
[0031] A porous SiC catalyst loaded with Pt nanoparticles, the preparation method of which is as follows:
[0032] (1) 3 g of polycrystalline silicon carbide was chemically etched with a mixed acid formed by 30 mL of hydrofluoric acid and concentrated nitric acid. After the etching was completed, it was then washed with water and dried, and then calcined in air at 700° C. for 3 h. After the calcination was completed, the calcined product was immersed in hydrofluoric acid to remove silicon dioxide, and finally washed with water until neutral and dried to obtain a porous silicon carbide carrier;
[0033] (2) The porous silicon carbide carrier and chloroplatinic acid hexahydrate were added to deionized water, stirred evenly, and placed in a rotary evaporator, and vacuum-evaporated at room temperature for 30 minutes. After the rotary evaporation was completed, the lysine solution was added dropwise into the rotary evaporator. After the addition was completed, the mixture was stirred for 30 minutes. Then, the reducing agent aqueous solution and hydrochloric acid were added dropwise into the rotary evaporator in sequence. After the addition was completed, the mixture was stirred for 24 hours. After the reaction was completed, the reaction solution was filtered, washed with deionized water 3 times, washed with ethanol aqueous solution 3 times, and dried to obtain a porous SiC catalyst (denoted as Pt / SiC-3) with a specific surface area of 135 m 2 / g, and the surface Si / C ratio is 0.997.
[0034] The usage ratio of the porous silicon carbide carrier to chloroplatinic acid hexahydrate, deionized water, lysine solution, reducing agent aqueous solution, and hydrochloric acid is 294 mg: 3.99 mg: 30 mL: 20 mL: 10 mL: 10 mL;
[0035] The lysine solution is a solution with a concentration of 0.53 mol / L formed by dissolving lysine in deionized water;
[0036] The reducing agent aqueous solution is a solution having a concentration of 0.35 mol / L obtained by adding a reducing agent into deionized water;
[0037] The concentration of the hydrochloric acid is 0.3 mol / L.
[0038] The reducing agent is sodium borohydride.
[0039] The volume ratio of hydrofluoric acid to nitric acid in the mixed acid is 3:1, the mass concentration of hydrofluoric acid is 40%, and the mass concentration of nitric acid is 65%.
[0040] The etching temperature range in step (1) is 100°C.
[0041] The etching time in step (1) is 3 h.
[0042] 30 mg of Pt / SiC-3 was weighed and placed in a stainless steel high-pressure reactor. 9.5 mL of anhydrous ethanol, 0.5 mL of water and 1 mmol of cinnamaldehyde were added. The high-pressure reactor was sealed and purged with hydrogen three times. Hydrogen was then filled into the reactor to a pressure of 0.4 MPa. The reactor was then heated to 40°C while magnetically stirring. The reaction was stirred at a constant temperature for 75 minutes. After the reaction was completed, the conversion rate of cinnamaldehyde was detected to be 98%, and the selectivity of cinnamyl alcohol was 96.7%.
[0043] Comparative Example 1 is the same as Example 1, except that the catalyst preparation method in Comparative Example 1 is as follows:
[0044] Polycrystalline silicon carbide and chloroplatinic acid hexahydrate were added to deionized water, stirred evenly, and placed in a rotary evaporator, and vacuum-evaporated for 30 minutes at room temperature. After the rotary evaporation, lysine solution was added dropwise in the rotary evaporator. After the addition was completed, it was stirred for 30 minutes. Then, the reducing agent aqueous solution and hydrochloric acid were added dropwise in the rotary evaporator in turn. After the addition was completed, the reaction was stirred for 24 hours. After the reaction was completed, the reaction solution was filtered, washed with deionized water 3 times, washed with ethanol aqueous solution 3 times, and dried to obtain Pt / SiC-0, which has a specific surface area of 27m 2 / g, and the surface Si / C ratio is 0.885.
[0045] The usage ratio of the polycrystalline silicon carbide to chloroplatinic acid hexahydrate, deionized water, lysine solution, reducing agent aqueous solution, and hydrochloric acid is 294 mg: 3.99 mg: 30 mL: 20 mL: 10 mL: 10 mL;
[0046] The lysine solution is a solution with a concentration of 0.53 mol / L formed by dissolving lysine in deionized water;
[0047] The reducing agent aqueous solution is a solution having a concentration of 0.35 mol / L obtained by adding a reducing agent into deionized water;
[0048] The concentration of the hydrochloric acid is 0.3 mol / L.
[0049] The reducing agent is sodium borohydride.
[0050] The volume ratio of hydrofluoric acid to nitric acid in the mixed acid is 3:1, the mass concentration of hydrofluoric acid is 40%, and the mass concentration of nitric acid is 68%.
[0051] 30 mg Pt / SiC-0 was weighed and placed in a stainless steel high-pressure reactor, 9.5 mL ethanol, 0.5 mL water and 1 mmol cinnamaldehyde were added, the high-pressure reactor was sealed and purged with hydrogen three times, and then hydrogen was filled into the reactor to a pressure of 0.4 MPa. Then, the temperature of the reactor was heated to 40°C while magnetically stirring, and the reaction was stirred at a constant temperature for 75 minutes. After the reaction, the conversion rate of cinnamaldehyde was detected to be 60.9%, and the selectivity of cinnamyl alcohol was 70.4%.
[0052] Comparative Example 2 is the same as Example 1, except that the etching time in step (1) of Comparative Example 2 is 2 h. The obtained catalyst is denoted as Pt / SiC-2. Its specific surface area is 79 m 2 / g, and the surface Si / C ratio is 0.983.
[0053] 30 mg of Pt / SiC-2 was weighed and placed in a stainless steel high-pressure reactor. 9.5 mL of anhydrous ethanol, 0.5 mL of water and 1 mmol of cinnamaldehyde were added. The high-pressure reactor was sealed and purged with hydrogen three times. Hydrogen was then filled into the reactor to a pressure of 0.4 MPa. The reactor was then heated to 40°C while magnetically stirring. The reaction was stirred at a constant temperature for 75 minutes. After the reaction was completed, the conversion rate of cinnamaldehyde was detected to be 79.6%, and the selectivity of cinnamyl alcohol was 91%.
[0054] Comparative Example 3 is the same as Example 1, except that the etching time in step (1) of Comparative Example 3 is 4 h. The obtained catalyst is denoted as Pt / SiC-4. Its specific surface area is 27 m 2 / g, and the surface Si / C ratio is 0.968.
[0055] 30 mg of Pt / SiC-2 was weighed and placed in a stainless steel high-pressure reactor, 9.5 mL of anhydrous ethanol, 0.5 mL of water and 1 mmol of cinnamaldehyde were added, the high-pressure reactor was sealed and purged with hydrogen three times, and then hydrogen was filled into the reactor to a pressure of 0.4 MPa. Then, the temperature of the reactor was heated to 40°C while magnetically stirring, and the reaction was stirred at a constant temperature for 75 minutes. After the reaction, it was detected that the conversion rate of cinnamaldehyde was 85.9%, and the selectivity of cinnamyl alcohol was 94.8%.
[0056] The data obtained by testing Example 1 and Comparative Examples 1-3 are shown in Table 1.
[0057] Table 1
[0058]
[0059] As can be seen from Table 1, the acid etching time has a great influence on the performance of the catalyst. With the increase of etching time, the specific surface area of the catalyst gradually increases, which is more conducive to the uniform dispersion and anchoring of Pt nanoparticles. At the same time, the Si / C ratio also changes. When the proportion of Si atoms increases, the hydrogen overflow capacity of the catalyst is enhanced, and its catalytic activity is significantly improved. When the etching time is 3h, the performance of Pt / SiC-3 catalyzing the hydrogenation of cinnamaldehyde to prepare cinnamyl alcohol is the best.
[0060] The Pt / SiC-3 obtained in Example 1 was used as a catalyst in the hydrogenation reaction of cinnamaldehyde, and the catalytic activity of Pt / SiC-3 in different alcohol solvents for 1 h of hydrogenation reaction of cinnamaldehyde was investigated. The test results are shown in Table 2.
[0061] Comparative Example 4 is the same as Example 1, except that the alcohol solvent in Comparative Example 4 is anhydrous ethanol. The cinnamaldehyde hydrogenation reaction is carried out for 1 hour. After the reaction is completed, it is detected that the conversion rate of cinnamaldehyde is 59.2%, and the selectivity of cinnamyl alcohol is 88.9%.
[0062] Comparative Example 5 is the same as Example 1, except that the alcohol solvent in Comparative Example 5 is isopropanol. The cinnamaldehyde hydrogenation reaction was carried out for 1 hour. After the reaction, it was detected that the conversion rate of cinnamaldehyde was 29.2%, and the selectivity of cinnamyl alcohol was 81.6%.
[0063] Comparative Example 6 is the same as Example 1, except that the alcohol solvent in Comparative Example 6 is methanol. The cinnamaldehyde hydrogenation reaction is carried out for 1 hour. After the reaction is completed, it is detected that the conversion rate of cinnamaldehyde is 32.3%, and the selectivity of cinnamyl alcohol is 86%.
[0064] Comparative Example 7 is the same as Example 1, except that the alcohol solvent in Comparative Example 7 is methanol. The cinnamaldehyde hydrogenation reaction is carried out for 1 hour. After the reaction is completed, it is detected that the conversion rate of cinnamaldehyde is 32.3%, and the selectivity of cinnamyl alcohol is 86%.
[0065] Comparative Example 8 is the same as Example 1, except that the alcohol solvent in Comparative Example 8 is a mixed solution of anhydrous ethanol and water in a volume ratio of 9.5:0.5. The cinnamaldehyde hydrogenation reaction was performed for 1 hour. After the reaction, the conversion rate of cinnamaldehyde was detected to be 79.0%, and the selectivity of cinnamyl alcohol was 94.8%.
[0066] Comparative Example 9 is the same as Example 1, except that the alcohol solvent in Comparative Example 9 is a mixed solution of anhydrous ethanol and water in a volume ratio of 9:1. The cinnamaldehyde hydrogenation reaction was performed for 1 hour. After the reaction, the conversion rate of cinnamaldehyde was detected to be 83.7%, and the selectivity of cinnamyl alcohol was 91.7%.
[0067] Table 2
[0068]
[0069] It can be seen from Table 2 that the addition of a small amount of H2O is beneficial to the selective hydrogenation of cinnamaldehyde molecules, which can promote the hydrogen overflow effect and thus enhance the catalytic hydrogenation activity, but too much water will lead to a decrease in the selectivity of cinnamyl alcohol.
[0070] The Pt / SiC-3 obtained in Example 1 was used as a catalyst in the hydrogenation reaction of cinnamaldehyde, and the catalytic activity of Pt / SiC-3 in the hydrogenation reaction of cinnamaldehyde for 1 h at different hydrogenation pressures was investigated. The test results are shown in Table 3.
[0071] Comparative Example 10 is the same as Example 1, except that the hydrogen filling pressure in Comparative Example 10 is 0.4 MPa. After the cinnamaldehyde hydrogenation reaction is performed for 1 hour, the conversion rate of cinnamaldehyde is detected to be 79%, and the selectivity of cinnamyl alcohol is 94.8%.
[0072] Comparative Example 11 is the same as Example 1, except that the hydrogenation pressure in Comparative Example 11 is 0.6 MPa. After the cinnamaldehyde hydrogenation reaction is performed for 1 hour, the conversion rate of cinnamaldehyde is detected to be 89.8%, and the selectivity of cinnamyl alcohol is 90.2%.
[0073] Comparative Example 12 is the same as Example 1, except that the hydrogen filling pressure in Comparative Example 12 is 0.8 MPa. After the cinnamaldehyde hydrogenation reaction is performed for 1 hour, the conversion rate of cinnamaldehyde is detected to be 95.2%, and the selectivity of cinnamyl alcohol is 89.8%.
[0074] Table 3
[0075] Hydrogen filling pressure (MPa) Conversion rate (%) Selectivity (%) 0.4 79 94.8 0.6 89.8 90.2 0.8 95.2 89.8
[0076] It can be seen from Table 3 that, under the same catalyst condition, as the hydrogen pressure increases, the conversion rate of cinnamaldehyde gradually increases, but the selectivity for cinnamyl alcohol product decreases. Therefore, the optimal reaction pressure is 0.4 MPa.
[0077] Comparative Example 13 is the same as Example 1, except that the method of step (2) of Comparative Example 13 is as follows:
[0078] A porous silicon carbide carrier and chloroplatinic acid hexahydrate are added to deionized water, stirred evenly, and then lysine solution is added dropwise. After the addition is completed, it is stirred for 30 minutes. Then, a reducing agent aqueous solution and hydrochloric acid are added dropwise to the reaction system in sequence. After the addition is completed, the reaction is stirred for 24 hours. After the reaction is completed, the reaction liquid is filtered, washed with deionized water 3 times, washed with ethanol aqueous solution 3 times, and dried to obtain a porous SiC catalyst.
[0079] 30 mg of porous SiC catalyst was weighed and placed in a stainless steel high-pressure reactor, 9.5 mL of anhydrous ethanol, 0.5 mL of water and 1 mmol of cinnamaldehyde were added, the high-pressure reactor was sealed and purged with hydrogen three times, and then hydrogen was filled into the reactor to a pressure of 0.4 MPa. Then, the temperature of the reactor was heated to 40°C while magnetically stirring, and the reaction was stirred at a constant temperature for 75 minutes. After the reaction, it was detected that the conversion rate of cinnamaldehyde was 96.9%, and the selectivity of cinnamyl alcohol was 80.7%.
[0080] The microscopic morphology of the catalyst carriers in Example 1 and Comparative Examples 1-2 was studied using a high-resolution electron microscope (HRTEM). Figure 1 As shown in the figure, Figure a is the morphology before etching, Figure b is the morphology after etching for 2 hours, and Figure c is the morphology after etching for 3 hours. It can be seen from the figure that with the increase of etching time, the pores on the SiC surface gradually increase, showing an obvious porous structure.
[0081] HRTEM of Pt / SiC-3 is as attached in the instruction manual Figure 2 As shown in the figure, it can be seen that the Pt nanoparticles are uniformly dispersed on the porous SiC, and the average particle size is about 4nm.
[0082] The XRD patterns of the catalysts obtained in Example 1 and Comparative Examples 1-3 are shown in the attached specification. Figure 3 As shown in the figure, the diffraction peaks at 35.6°, 41.4°, 60.0°, 71.8° and 75.5° correspond to the (111), (200), (220), (311) and (222) crystal planes of β-SiC, respectively. No obvious diffraction peak of Pt is seen, which may be because the Pt particles are small in size and evenly distributed.
[0083] Based on the above ideal embodiments of the present invention, the relevant staff can make various changes and modifications without departing from the technical concept of the present invention through the above description. The technical scope of the present invention is not limited to the contents of the specification, and its technical scope must be determined according to the scope of the claims.
Claims
1. A porous SiC catalyst supported by Pt nanoparticles, characterized in that: The preparation method comprises the following steps: (1) chemically etching polycrystalline silicon carbide with a mixed acid formed by hydrofluoric acid and concentrated nitric acid, washing with water, drying, and then calcining in air at 700-1100° C. for at least 3 hours. After calcination, soaking the calcined product in hydrofluoric acid to remove silicon dioxide, and finally washing with water to neutrality and drying to obtain a porous silicon carbide carrier; (2) adding a porous silicon carbide carrier and chloroplatinic acid to deionized water, stirring evenly, placing in a rotary evaporator, vacuum evaporating at room temperature for at least 30 minutes, adding lysine solution dropwise into the rotary evaporator after the addition is complete, stirring for at least 30 minutes, then adding a reducing agent aqueous solution and hydrochloric acid dropwise into the rotary evaporator in sequence, stirring for at least 24 hours after the addition is complete, after the reaction is complete, filtering the reaction solution, washing with deionized water at least 3 times, washing with ethanol aqueous solution at least 3 times, and drying to obtain a porous SiC catalyst; The usage ratio of the porous silicon carbide carrier to chloroplatinic acid, deionized water, lysine solution, reducing agent aqueous solution, and hydrochloric acid is 290-295 mg: 15-17 mg: 30 mL: 20 mL: 10 mL: 10 mL; The lysine solution is a solution with a concentration of 0.5-0.55 mol / L formed by dissolving lysine in deionized water; The reducing agent aqueous solution is a solution having a concentration of 0.3-0.4 mol / L obtained by adding the reducing agent into deionized water; The concentration of the hydrochloric acid is 0.25-0.35 mol / L.
2. The porous SiC catalyst supported by Pt nanoparticles according to claim 1, characterized in that: The reducing agent is sodium borohydride.
3. The porous SiC catalyst supported by Pt nanoparticles according to claim 1, characterized in that: The volume ratio of hydrofluoric acid to nitric acid in the mixed acid is 3:1, the mass concentration of hydrofluoric acid is 40%, and the mass concentration of nitric acid is 65-68%.
4. The Pt nanoparticle-supported porous SiC catalyst according to claim 1, characterized in that: The etching temperature in step (1) ranges from 60 to 120°C.
5. The Pt nanoparticle-supported porous SiC catalyst according to claim 1, characterized in that: The etching time in step (1) is 1-4 hours.
6. The Pt nanoparticle-supported porous SiC catalyst according to claim 5, characterized in that: The etching time in step (1) is 3 h.
7. An application of a porous SiC catalyst supported by Pt nanoparticles, characterized in that: The following steps are involved: The porous SiC catalyst obtained according to any one of claims 1 to 6 is weighed and placed in a stainless steel high-pressure reactor, an alcohol solvent and cinnamaldehyde are added, the high-pressure reactor is sealed and purged with hydrogen for 3 times, hydrogen is filled into the reactor to a pressure of 0.4-0.8 MPa, and then the temperature of the reactor is heated to 30-60° C. while magnetically stirring, and the reaction is carried out by constant temperature stirring for 30-90 minutes. After the reaction is completed, cinnamyl alcohol is obtained after purification.
8. The use of a Pt nanoparticle-supported porous SiC catalyst according to claim 7, characterized in that: The alcohol solvent includes at least one of anhydrous ethanol, isopropanol, methanol and a mixed solvent formed by ethanol and water.
9. The use of a Pt nanoparticle-supported porous SiC catalyst according to claim 8, characterized in that: The alcohol solvent is a mixed solvent formed by ethanol and water.
10. The use of a Pt nanoparticle-supported porous SiC catalyst according to claim 9, characterized in that: The volume ratio of ethanol to water in the alcohol solvent is 9-9.5:0.5-1.
Citation Information
Patent Citations
Preparation method for silicon carbide loaded metal nanoparticle catalyst
CN102728397A
Porous nano-SiC loaded platinum catalyst as well as preparation and application thereof in selective hydrogenation reaction of Alpha-Beta-unsaturated aldehyde
CN105618095A
High-performance platinum-titanium monatomic catalyst as well as preparation method and application thereof
CN114471539A
Surface modified Pt / SiC catalyst, preparation method and electrochemical oxidation device
CN114950515A
Method for preparing non-porous metal catalyst by photodeposition method and application of catalyst
CN119098166A